Biodegradation of Lambda Cyhalothrin by Ralstonia eutropha - Uslu, Gülşad; Özdemir-Atay, Irem (American Society of Agricultural and Biological Engineers, 2013)
In this study, biodegradation of Lambda C by free Ralstonia eutropha was performed in batch system Glucose was used as carbon source in addition to pesticides. The effects of initial pH, temperature and initial pesticides concentrations on the substrate removal and specific growth rates and yields were investigated. Optimum initial lambda c concentrations, initial pH and temperature were determined as 2 mg-1, 6 and 20°C, respectively for free cells. In these optimum conditions, the maximum microorganism's specific growth and pesticide removal rates were determined as 0,0878 h -1 and 0,0408 mg/g dry cell/h for lambda c., respectively. Lambda C had a strong inhibitory effect on the microbial growth, substrate inhibition was observed at concentrations higher pesticide concentrations than 2 mg/L. At experiments, where substrate inhibition was not observed, microorganism's specific growth was implied with Monod Equality depending on substrate concentration. In these conditions, microorganisms inhibition constant values was determined as Ks= 0,8540 for lambda c. The results show that the growth of R. eutropha was not effective for biodegration of Lambda C.
American Society of Agricultural and Biological Engineers Annual International Meeting 2013 -- 21 July 2013 through 24 July 2013 -- Kansas City, MO -- 98427
Keywords: Biodegradation; Inhibition; Lambda C; Specific growth rate